The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1145/1232743.1232773
|View full text |Cite
|
Sign up to set email alerts
|

Does telecommuting improve productivity?

Abstract: Seeking solid evidence of demonstrable productivity gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 2 publications
(5 reference statements)
1
10
0
4
Order By: Relevance
“…These findings continue to be supported by new research showing that telework increases productivity (Butler, Aasheim, & Williams, 2007;Neufeld & Fang, 2005) and enhances client satisfaction and employee attraction to an organization (Verive & Paul-Heelan, 2006).…”
Section: Telework and Business Outcomesmentioning
confidence: 60%
“…These findings continue to be supported by new research showing that telework increases productivity (Butler, Aasheim, & Williams, 2007;Neufeld & Fang, 2005) and enhances client satisfaction and employee attraction to an organization (Verive & Paul-Heelan, 2006).…”
Section: Telework and Business Outcomesmentioning
confidence: 60%
“…A positive work-life environment has a positive impact on the development of this country through enhancing individuals' participation in economic activities. For example, studies have shown that through teleworking organizations can structure their operations to cut costs, maximize resources and improve productivity, develop pools of professional candidates who were physically inaccessible in the past, and by hiring workers under various contractual arrangements, including overseas employees, can offer a better quality of work and many financial benefits (Butler et al, 2007;Crandal & Gao, 2005;Gibson et al, 2002;Harpaz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…With the flexibility of time, teleworkers can choose to work when they are most energetic or have the fewest distractions. An alternative viewpoint is that teleworkers are more productive because they have additional training or were selected to telework because they were already the most productive employees (Butler, Aasheim, & Williams, 2007). Most studies claiming increased productivity are based on self-reported data, but it seems reasonable that workers who were solid contributors to the workplace before they teleworked and who now have the trust of their supervisors are likely to be more productive than they were when tethered to their office desks.…”
Section: Employer Advantagesmentioning
confidence: 99%